2020
DOI: 10.3390/su12219014
|View full text |Cite
|
Sign up to set email alerts
|

To Mod or Not to Mod—An Empirical Study on Game Modding as Customer Value Co-Creation

Abstract: A spiking interest in customer’s value co-creation may be observed lately, especially in the gaming industry. The general purpose of this study is to identify the customers’ inclination to perform game modding as a manner of value co-creation which benefits both companies and other game users. The current knowledge regarding the factors determining this behaviour is, relatively speaking, weak. The authors conducted qualitative research in the forms of in-depth interviews and focus groups with Polish game playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
(85 reference statements)
1
3
0
2
Order By: Relevance
“…Users are seeking personal accomplishments in online gaming communities in order to enhance their chances of gaining recognition, social status and possibly greater roles (e.g,. community moderators) (Bilińska-Reformat et al, 2020;Dewalska-Opitek & Hofman-Kohlmeyer, 2021). Our findings support other studies indicating that personal incentives, such as achieving a sense of self-efficacy and self-esteem as well as enhancing reputation, provide strong opportunities for consumer engagement (Chen, Liu et al, 2019;Nambisan & Baron, 2009;Qin, 2020;Whiting & Williams, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Users are seeking personal accomplishments in online gaming communities in order to enhance their chances of gaining recognition, social status and possibly greater roles (e.g,. community moderators) (Bilińska-Reformat et al, 2020;Dewalska-Opitek & Hofman-Kohlmeyer, 2021). Our findings support other studies indicating that personal incentives, such as achieving a sense of self-efficacy and self-esteem as well as enhancing reputation, provide strong opportunities for consumer engagement (Chen, Liu et al, 2019;Nambisan & Baron, 2009;Qin, 2020;Whiting & Williams, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…With the expansion of the gaming industry, online communities became an essential factor reinforcing value co-creation mechanisms (Bilińska-Reformat et al, 2020;Thorhauge & Nielsen, 2021). A key example could be found in the success of "sandbox" games, where users are able to create their own projects within an open world (exp.…”
Section: Value Co-creationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that certain motives (e.g. achievement and escapism) are factors correlated with gaming time to a greater extent than other motives among western MMORPG players (Billieux et al 2011;Dauriat et al 2011;Yee 2006a). One may also observe the phenomenon of prosumption, based on the participation of players in game improvements -there is tentative evidence for customers' motivations to co-create games, which benefits both companies (game developers) and other game users (Bilińska-Reformat, Dewalska-Opitek & Hofman-Kohlmeyer 2020).…”
Section: Motives For Playing In Light Of Literaturementioning
confidence: 99%
“…Embora os jogos tenham o potencial de melhorar as práticas educacionais, o desenvolvimento de tais jogos é muitas vezes uma tarefa demorada e complicada, necessitando do envolvimento de numerosos especialistas e custando uma quantidade significativa de tempo e dinheiro [Bilińska-Reformat et al 2020]. Como resultado da natureza demorada e financeiramente custosa deste procedimento, os desenvolvedores de jogos educativos frequentemente priorizam a adaptac ¸ão de jogos pré-existentes ao invés do desenvolvimento de novos jogos [Abbott 2019].…”
Section: Introduc ¸ãOunclassified